Association of Proximity to a Long-Term Acute Care Hospital With Hospital Tracheostomy Practices. Issue 1 (January 2022) - Mehta, Anuj B.; Matlock, Daniel; Douglas, Ivor S.
Abstract : OBJECTIVES: Availability of long-term acute care hospitals has been associated with hospital discharge practices. It is unclear if long-term acute care hospital availability can influence patient care decisions. We sought to determine the association of long-term acute care hospital availability at different hospitals with the likelihood of tracheostomy. DESIGN: Retrospective cohort study. SETTING: California Patient Discharge Database, 2016–2018. PATIENTS: Adult patients receiving mechanical ventilation for respiratory failure. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Using the California Patient Discharge Database 2016–2018, we identified all mechanically ventilated patients and those who received tracheostomy. We determine the association between tracheostomy and the distance between each hospital and the nearest long-term acute care hospital and the number of long-term acute care hospital beds within 20 miles of each hospital. Among 281, 502 hospitalizations where a patient received mechanical ventilation, 22, 899 (8.1%) received a tracheostomy. Patients admitted to a hospital closer to a long-term acute care hospital compared with those furthest from a long-term acute care hospital had 38.9% (95% CI, 33.3–44.6%) higher odds of tracheostomy (closest hospitals 8.7% vs furthest hospitals 6.3%, adjusted odds ratio = 1.65; 95% CI, 1.40–1.95). Patients had a 32.4% (95% CI, 27.6–37.3%) higher risk of tracheostomy when admitted to a hospital with more long-term acute care hospital beds in the immediate vicinity (most long-term acute care hospital beds within 20 miles 8.9% vs fewest long-term acute care hospital beds 6.7%, adjusted odds ratio = 1.54; 95% CI, 1.31–1.80). Distance to the nearest long-term acute care hospital was inversely correlated with hospital risk-adjusted tracheostomy rates (ρ = –0.25; p < 0.0001). The number of long-term acute care hospital beds within 20 miles was positively correlated with hospital risk-adjusted tracheostomy rates (ρ = 0.22; p < 0.0001). CONCLUSIONS: Proximity and availability of long-term acute care hospital beds were associated with patient odds of tracheostomy and hospital tracheostomy practices. These findings suggest a hospital effect on tracheostomy decision-making over and above patient case-mix. Future studies focusing on shared decision-making for tracheostomy are needed to ensure goal-concordant care for prolonged mechanical ventilation. Abstract : Supplemental Digital Content is available in the text.